Genomic and Experimental Evidence Suggests that Verrucomicrobium spinosum Interacts with Eukaryotes - Sait, Michelle; Kamneva, Olga; Fay, David; Kirienko, Natalia; Polek, James; Shirasu-Hiza, Mimi; Ward, Naomi L. (Frontiers in Microbiology, 2011)
Our knowledge of pathogens and symbionts is heavily biased towards phyla containing species that are straightforward to isolate in pure culture. Novel bacterial phyla are often represented by a handful of strains, and the number of species interacting with eukaryotes is likely underestimated. Identification of predicted pathogenesis and symbiosis determinants such as the Type III Secretion System (T3SS) in the genomes of ‘free-living’ bacteria suggests that these microbes participate in uncharacterized interactions with eukaryotes. Our study aimed to test this hypothesis on Verrucomicrobium spinosum (phylum Verrucomicrobia) and to begin characterization of its predicted T3SS. We showed the putative T3SS structural genes to be transcriptionally active, and that expression of predicted effector proteins was toxic to yeast in an established functional screen. Our results suggest that the predicted T3SS genes of V. spinosum could encode a functional T3SS, although further work is needed to determine whether V. spinosum produces a T3SS injectisome that delivers the predicted effectors. In the absence of a known eukaryotic host, we made use of invertebrate infection models. The injection or feeding of V. spinosum to Drosophila melanogaster and Caenorhabiditis elegans, respectively, was shown to result in increased mortality rates relative to controls, a phenomenon exaggerated in C. elegans mutants hypersensitive to pathogen infection. This finding, although not conclusively demonstrating pathogenesis, suggests that V. spinosum is capable of pathogenic activity towards an invertebrate host. Symbiotic interactions with a natural host provide an alternative explanation for the results seen in the invertebrate models. Further work is needed to determine whether V. spinosum can establish and maintain interactions with eukaryotic species found in its natural habitat, and whether the predicted T3SS is directly involved in pathogenic or symbiotic activity.